Variability in high temperature induced pollen and spikelet sterility to affect productivity of rice (Oryza sativa L.) genotypes - Hilali, Hilali Saleh; Thind, S K; Manghat, G S (ORYZA-An International Journal of Rice, 2019)
High temperature has profound effect on productivity of rice (Oryza sativa L.). To face the challenges of global warming and increase the area under rice cultivation genotypes that can withstand high temperature are to be identified. In this study, twenty rice genotypes with different origin (viz. Balilla, Cuiabara, Ganja, Rangwala, Ganjay, IR 6, IR 61250, IR 65192, IR 2006, IR 2307, IR28, IR50, IR72, Sadri, Sahel 108, Tak Ratia, PR 121, PR 122, PR 123, PB1121 and PPB 1509) were sown in the first week of March (stress environment) and last week of May (normal environment) following randomized complete block design with three replications. Pollen sterility was significantly increased under stress environment in all the genotypes and most severe effect was recorded in Tak Ratia. The percent spikelet sterility ranged from 8.8% to 100% with values 73% and 100% in Tak Ratia and PB1121 respectively. PR121, PR122 and IR 2307 maintained low percent spikelet sterility under stress and sustained productivity. The genotypes did not have significant difference in thousand grain weightunder normal and stress environment. The study revealed that high temperature increased the pollen sterility and these were unable to germinate on stigma thus increasing the spikelet sterility that led to decreased productivity in selected rice genotypes. The genotypes PR121, Ganjay, PR122 and IR2307 due to better performance under stress were selected for cultivation under high temperature conditions.